PEMBENTUKAN KETERAMPILAN MENULIS NONFIKSI SISWA KELAS V SDN 069 CIPAMOKOLAN JAWA BARAT MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF - Ani Kusmayani (Jurnal Literasi Pendidikan Dasar, 2023)
Most students' writing that is poorly organized and lacks essential details demonstrates their lack of writing proficiency. It was caused by the used of conventional learning, that it does not involve the acquisition of any new information or resources and the teacher maintains a preeminent role in the learning process. The focus of this study is on how the cooperative learning model can be used to enhance students' composing abilities. Students at SDN 069 Cipamokolan's fifth grade participated in the research. Class action research is being used in this study. The findings of this study support the claim that the cooperative learning model can be used to boost the students' writing abilities in the fifth grade at State Elementary School 069 Cipamokolan. From 25% in the pre-cycle to 50% in the cycle I, the percentage of students who handed in complete writing assignments rose significantly. Then, in cycle II, 91% of students managed to finish the assignment. Fifth graders' writing skills can increase from using the cooperative learning model, so that's what we'll do here at SDN 069 Cipamokolan. Students can benefit from active learning, peer interaction, and peer support through the use of participatory learning strategies. It is hoped that teachers of elementary school students can use cooperative learning strategy to help their students become better non-fictive writers.